Vertebral artery dissection in evolution found during chiropractic examination. (12th November 2015) - Futch, Dan; Schneider, Michael J; Murphy, Donald; Grayev, Allison
Abstract : A 30-year-old woman presented to an emergency department with sudden onset of transient loss of left peripheral vision. Owing to a history of migraine headaches, she was released with a diagnosis of ocular migraine. Two days later, she sought chiropractic care for the chief symptom of severe neck pain. The chiropractor suspected the possibility of vertebral artery dissection (VAD). No manipulation was performed; instead, MR angiography (MRA) of the neck was obtained, which revealed an acute left VAD with early thrombus formation. The patient was placed on aspirin therapy. Repeat MRA of the neck 3 months later revealed resolution of the thrombus, without progression to stroke. This case illustrates the importance for all healthcare providers who see patients with neck pain and headache to be attentive to the symptomatic presentation of possible VAD in progress.